Bilingualism and Multilingualism in Street Level Social Welfare Service Settings: A Scoping Review - Larjanko, Leo; Pötzsch, Tobias; Granholm, Camilla; Julkunen, Ilse (Routledge, 2025)
Multilingualism receives limited support in welfare systems, as shifting migration and rising nationalism complicate its management despite varying policy recognition across countries. This scoping review contributes to the growing body of literature on language and social welfare by examining how bilingualism and multilingualism are negotiated by street-level bureaucrats in their interactions with clients. While formal language policy is rarely shaped at the front lines of welfare services, street-level bureaucrats play a crucial role in its implementation, often exercising significant discretion that directly impacts client experiences. We searched for peer-reviewed, English language articles addressing multilingualism in social welfare work and the searches yielded 441 articles. Data extracted from 13 articles are presented. Qualitative content analysis was used to analyze the 13 selected using Hult and Hornberger’s ([2016]. “Revisiting Orientations in Language Planning: Problem Right, and Resource as an Analytical Heuristic.” Bilingual Review/Revista Bilingüe 33:3) adaptation of Richard Ruiz’s ([1984]. “Orientations in Language Planning.” NABE Journal 8 (2): 15–34. https://doi.org/10.1080/08855072.1984.10668464; “Reorienting Language-as-Resource.” In International Perspectives on Bilingual Education: Policy, Practice, and Controversy, edited by J. E. Petrovic, 155–172. Charlotte, NC: Information Age) three orientations to language planning. Findings reveal that all three orientations are present to varying extents, influencing both how bilingual professionals perceive language and how they interpret the treatment of clients. Notably, the prevalence of the ‘language as problem' orientation raises ethical concerns, whereas the ‘language as right' and ‘language as resource' perspectives offer more ethically sound foundations for inclusive and equitable social welfare work.